Age-related effects on the modulation of gut microbiota by pectins and their derivatives: an in vitro study - Gu, Fangjie; Larsen, Nadja; Pascale, Nélida; Petersen, Sune Allan; Khakimov, Bekzod; Respondek, Frederique; Jespersen, Lene (Frontiers in Microbiology, 2023)
The present study investigates whether supplementation with pectin-type polysaccharides has potential to improve aging-associated dysbiosis of the gut microbiota. The influence of different types of pectins on the gut microbiota composition and short-chain fatty acids (SCFAs) profiles of elderly was compared to younger adults. Pectins studied included a pectin polysaccharide (PEC), a partially hydrolyzed pectin (PPH), and a pectin oligosaccharide (POS). Additionally, inulin was used as a reference prebiotic substrate. Individual fecal samples were collected from healthy elderly volunteers (70-75 years) and younger adults (30-35 years). In vitro fermentations were performed using the CoMiniGut model with controlled temperature and pH. Samples were withdrawn at baseline and after 24 h fermentation for measurement of SCFAs production and microbiota composition by 16S rRNA gene sequencing. The results showed that fermentations with PEC and PPH resulted in a specific stimulation of Faecalibacterium prausnitzii regardless of the age groups. Collinsella aerofaciens became a dominating species in the young adult group with fermentations of all three pectins, which was not observed in the elderly group. No significant differences in SCFAs production were found among the pectins, indicating a high level of functional redundancy. Pectins boosted various bacterial groups differently from the reference prebiotic substrate (inulin). We also found inulin had reduced butyrogenic and bifidogenic effects in the elderly group compared to the younger adult group. In conclusion, the in vitro modulating effects of pectins on elderly gut microbiota showed potential of using pectins to improve age-related dysbiosis.